Consequences of Sphaeropsis tip blight disease for the phytohormone profile and antioxidative metabolism of its pine host. (23rd February 2018) - Hu, Bin; Sakakibara, Hitoshi; Kojima, Mikiko; Takebayashi, Yumiko; Bußkamp, Johanna; Langer, Gitta J.; Peters, Franziska S.; Schumacher, Jörg; Eiblmeier, Monika; Kreuzwieser, Jürgen; Rennenberg, Heinz
Abstract: Phytopathogenic fungi infections induce plant defence responses that mediate changes in metabolic and signalling processes with severe consequences for plant growth and development. Sphaeropsis tip blight, induced by the endophytic fungus Sphaeropsis sapinea that spreads from stem tissues to the needles, is the most widespread disease of conifer forests causing dramatic economic losses. However, metabolic consequences of this disease on bark and wood tissues of its host are largely unexplored. Here, we show that diseased host pines experience tissue dehydration in both bark and wood. Increased cytokinin and declined indole‐3‐acetic acid levels were observed in both tissues and increased jasmonic acid and abscisic acid levels exclusively in the wood. Increased lignin contents at the expense of holo‐cellulose with declined structural biomass of the wood reflect cell wall fortification by S. sapinea infection. These changes are consistent with H2 O2 accumulation in the wood, required for lignin polymerization. Accumulation of H2 O2 was associated with more oxidized redox states of glutathione and ascorbate pools. These findings indicate that S. sapinea affects both phytohormone signalling and the antioxidative defence system in stem tissues of its pine host during the infection process. Abstract : Phytopathogenic fungi infections induce plant defence responses that mediate changes in metabolic and signalling processes with severe consequences for plant growth and development. In this study, we show that Sphaeropsis tip blight diseased host pines, induced by the endophytic fungus Sphaeropsis sapinea, experience the following: tissue dehydration in both bark and wood; increased cytokinin and declined indole‐3‐acetic acid levels in both tissues and increased jasmonic acid and abscisic acid levels exclusively in the wood; increased lignin contents at the expense of holo‐cellulose with declined structural biomass of the wood reflect cell wall fortification by S. sapinea infection; accumulation of H2 O2 associated with more oxidized redox states of glutathione and ascorbate pools. Such findings indicate that S. sapinea affects both phytohormone signalling and the antioxidative defence system in stem tissues of its pine host during the infection process.